2023
DOI: 10.1186/s13098-023-01011-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of estimated pulse wave velocity for cardiovascular and all-cause mortality in individuals with obesity

Abstract: Background Estimated pulse wave velocity (ePWV) has revealed excellent performance in predicting cardiovascular disease (CVD) risk. However, whether ePWV predicts all-cause mortality and CVD mortality in populations with obesity remains elusive. Methods We performed a prospective cohort including 49,116 participants from the National Health and Nutrition Examination Survey from 2005 to 2014. Arterial stiffness was evaluated by ePWV. Weighted univar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Compared with the mean PWV of 5.4 m/s for the age range of 45 to 50 [16], the mean PWV of 7.7 m/s of the presented case may indicate low vessel compliance due to a long-term exposure to components of MetS. The study of Li et al demonstrated a positive correlation between the estimated pulse wave velocity (ePWV) and all-cause mortality when the ePWV is greater than 6.7 m/s [12]. It is also important to note that a traditional 10 year Systematic Coronary Risk Evaluation (SCORE) scale may potentially underestimate cardiovascular risk in patients with diabetes, central obesity, low HDL, and elevated triglyceride levels [17,18].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Compared with the mean PWV of 5.4 m/s for the age range of 45 to 50 [16], the mean PWV of 7.7 m/s of the presented case may indicate low vessel compliance due to a long-term exposure to components of MetS. The study of Li et al demonstrated a positive correlation between the estimated pulse wave velocity (ePWV) and all-cause mortality when the ePWV is greater than 6.7 m/s [12]. It is also important to note that a traditional 10 year Systematic Coronary Risk Evaluation (SCORE) scale may potentially underestimate cardiovascular risk in patients with diabetes, central obesity, low HDL, and elevated triglyceride levels [17,18].…”
Section: Discussionmentioning
confidence: 52%
“…Kim et al investigated 848,498 people with MetS who underwent health screenings, and showed that a high serum gamma-glutamyl transferase associated with an impaired aortic elasticity in MetS, which accounts for a 50% increased risk of sudden cardiac death [11]. Similarly, Li et al, contingent on the National Health and Nutrition Examination Survey, reported that obesity as a single MetS component increased the PWV and elevated 5.76-fold the risk of cardiovascular mortality [12]. Moreover, Masrouri also reported a MetS population with a 1.4-to 1.6-fold increased risk of cardiac sudden death [13].…”
Section: Discussionmentioning
confidence: 99%
“…ePWV integrates age and blood pressure parameters, offering an accessible means to evaluate AS when compared to the complexities and expenses associated with cf-PWV. 36 Blood pressure and age represent readily accessible parameters that can be measured conveniently within community hospitals or even at home. This accessibility renders them particularly well-suited for risk assessment and healthcare management among individuals living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The BMI cut-off of 30 kg/m 2 universally identifies obesity and offers significant specificity. As such, this cut-off value continues to be used as a benchmark for statistical identification and classification of obesity in reports published by the WHO, the CDC, and the NIH, as well as in many studies [ 1 , 2 , 86 , 87 ]. This study also used this criterion to identify obesity, with a particular emphasis on the prognostic value of SIRI and SII on all-cause and CVD mortality in this population.…”
Section: Discussionmentioning
confidence: 99%